Islamic Leadership, Emotional Intelligence, and Workplace Spirituality: A Synergistic Model to Improve Teacher Productivity in Banyumas, Indonesia - Faridli, Efi Miftah; Bagis, Fatmah; Umairoh, Jovinda Percillia Ma'rifatul; Hamam, Zaki Nur (Ilomata International Journal of Management, 2026)
This study develops and tests a structural model linking Islamic leadership and emotional intelligence to teacher productivity, with workplace spirituality serving as a mediating variable. Grounded in Bandura’s Social Cognitive Theory, the research involved 250 teachers from Islamic-based secondary schools in the Ex-Residency area of Banyumas, Indonesia. Data were collected using standardized instruments and analyzed through Structural Equation Modeling with Partial Least Squares (SEM-PLS). The results indicate that both Islamic leadership and emotional intelligence significantly influence workplace spirituality and teacher productivity, both directly and indirectly. These findings highlight that work environments enriched with Islamic values, emotional competence, and spiritual meaning can enhance professional performance. This study contributes theoretically to the development of an integrative model and offers practical implications for educational policymakers to foster meaningful and sustainable school cultures.